'Can I borrow your glasses?': a prescription for learning to see the cultural roots of identity terms and implicit categories through others' lenses. Issue 6 (2nd November 2017) - Stevick, E. Doyle
Abstract: Why is there so much confusion and conflict around common identity labels, a problem that extends well beyond any stereotypes that they may evoke? How do we escape the seeming paradox that we reject racism but still speak frequently of black and white? Who claims the power to determine or name others' identities? The confusion and conflict about identity that play out on a surface level are often caused by starkly different but implicit understandings that operate beneath the surface. For example, terms like black, Jewish and Muslim may invoke several of our deeper conceptions or categories like race, culture, religion and ethnicity, and to varying degrees in different places. Critically, these categories themselves are culturally rooted. This article shows how our implicit categories can lead to both cross-cultural confusion and problematic misunderstandings in course content. Helping students to recognise and to understand the cultural roots of our implicit categories should be a deliberate learning outcome. This type of cultural understanding can be advanced significantly through guided reflection on experience and explicit instruction; in addition, some subjects and approaches – intercultural education, study abroad and Holocaust education among them – show particular promise for achieving this aim.